COZMIC. I. Cosmological Zoom-in Simulations with Initial Conditions Beyond Cold Dark Matter - Ethan O. Nadler; Rui An; Vera Gluscevic; Andrew Benson; Xiaolong Du (The Astrophysical Journal)
We present 72 cosmological dark-matter--only N -body zoom-in simulations with initial conditions beyond cold, collisionless dark matter (CDM), as the first installment of the COZMIC suite. We simulate Milky Way (MW) analogs with linear matter power spectra P ( k ) for (i) thermal-relic warm dark matter (WDM) with masses m _WDM  ∈ [3, 4, 5, 6, 6.5, 10]keV, (ii) fuzzy dark matter (FDM) with masses m _FDM  ∈ [25.9,69.4, 113, 151, 185, 490] × 10 ^−22 eV, and (iii) interacting dark matter (IDM) with a velocity-dependent elastic proton scattering cross section σ  =  σ _0 v ^n , relative particle velocity scaling n  ∈ [2, 4], and dark matter mass m _IDM  ∈ [10 ^−4 , 10 ^−2 , 1] GeV. Subhalo mass function (SHMF) suppression is significantly steeper in FDM versus WDM, while dark acoustic oscillations in P ( k ) can reduce SHMF suppression for IDM. We fit SHMF models to our simulation results and derive new bounds on WDM and FDM from the MW satellite population, obtaining m _WDM  > 5.9 keV and m _FDM  > 1.4 × 10 ^−20 eV at 95% confidence; these limits are ≈10% weaker and 5× stronger than previous constraints owing to the updated transfer functions and SHMF models, respectively. We estimate IDM bounds for n = 2 ( n = 4) and obtain σ _0  < 1.0 × 10 ^−27 cm ^2 , 1.3 × 10 ^−24 cm ^2 , and 3.1 × 10 ^−23 cm ^2 ( σ _0  < 9.9 × 10 ^−27 cm ^2 , 9.8 × 10 ^−21 cm ^2 , and 2.1 × 10 ^−17 cm ^2 ) for m _IDM  = 10 ^−4 , 10 ^−2 , and 1 GeV, respectively. Thus, future development of IDM SHMF models can improve IDM cross section bounds by up to a factor of ∼20 with current data. COZMIC presents an important step toward accurate small-scale structure modeling in beyond-CDM cosmologies, critical to upcoming observational searches for dark matter physics.